1998
DOI: 10.1104/pp.116.2.743
|View full text |Cite
|
Sign up to set email alerts
|

4-Coumarate:Coenzyme A Ligase in Hybrid Poplar1

Abstract: The enzyme 4-coumarate:coenzyme A ligase (4CL) is important in providing activated thioester substrates for phenylpropanoid natural product biosynthesis. We tested different hybrid poplar (Populus trichocarpa ؋ Populus deltoides) tissues for the presence of 4CL isoforms by fast-protein liquid chromatography and detected a minimum of three 4CL isoforms. These isoforms shared similar hydroxycinnamic acid substrate-utilization profiles and were all inactive against sinapic acid, but instability of the native form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(41 citation statements)
references
References 43 publications
2
37
0
2
Order By: Relevance
“…ScCCL had 44% identity and 58% similarity to A. thaliana 4CL2. Among the 4CL enzymes, two highly conserved peptide motifs, box I (SSGTTGLPKGV) and box II (GEICIRG), have been identified (1,2,10,11,18,26,28). In the ScCCL sequence, both motifs were also highly conserved.…”
Section: Resultsmentioning
confidence: 91%
“…ScCCL had 44% identity and 58% similarity to A. thaliana 4CL2. Among the 4CL enzymes, two highly conserved peptide motifs, box I (SSGTTGLPKGV) and box II (GEICIRG), have been identified (1,2,10,11,18,26,28). In the ScCCL sequence, both motifs were also highly conserved.…”
Section: Resultsmentioning
confidence: 91%
“…4), all of which exhibit a large structural, enzyme-kinetic, and apparent evolutionary diversity. The very opposite is exemplified by the much smaller and narrowly confined St4CL, Pc4CL, and Nt4CL families, which appear to consist of no more than two (St4CL) or three (Pc4CL, Nt4CL) nearly sequence-identical isoenzymes with indistinguishable substrate specificities (6,7,30). However, in all of these cases, with the single exception of At4CL, the true family sizes remain unknown until fully sequenced genomes are available.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the complexity and the extent of overlapping mRNA expression patterns that have been observed in various species for nearly all tested 4CL isoenzyme combinations (4,7,32,33), including At4CL1-3 (18), the pivotal position of 4CL in plant phenylpropanoid metabolism is probably reflected by a highly diversified metabolic grid (34)(35)(36). Moreover, the combination of distinct substrate preferences with differences in gene-promoter and protein fine structure may facilitate not only a large diversity of genetically programmed metabolic functions of the individual isoenzymes, including pathway-specific associations with biosynthetically related enzymes in metabolite channeling (37-39), but also regular or potential functional overlaps or mutual replacements upon malfunction or down-regulation, as has been investigated so far only for the class I isoforms (4,40,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So 4CL is one key enzyme of flavonodids biosynthesis pathway (Fan et al, 2007). Many studies revealed that 4cl gene was a multigene family: Two 4cl genes are cloned from Scutellaria baicalensis Georgi and three 4cl genes are isolated and characterized in Hyvrid Poplar (Allina et al, 1998). With further 4CL enzymological identification, genetic mutation and crystal modeling, the studies on the structure and evolution were implemented extensively (Cukovic et al, 2001;Schneider et al, 2003) and then some highly conserved enzyme active sites residues were revealed, such as Box I (SSGTTGLPKGV) and Box II (GEICIRG) (Stuible and Kombrink, 2001), sbd I (N-terminal domain) and abd II (C-terminal domain) .…”
Section: Introductionmentioning
confidence: 99%